EDUKASI PENERAPAN METODE HARGA PRODUK BERSAMA DAN SAMPINGAN UNTUK MENENTUKAN HARGA POKOK PRODUKSI DI UMKM PADA PABRIK TAHU 212 NAGARI CUPAK - Putri, Rita Dwi; Maison, Witra; Hikmah, Vinka Tahiyatul Nurul; Dani, Dillfa Lailatul Rahmi; Syahrila, Adinda Putri (MAJU : Indonesian Journal of Community Empowerment, 2025)
This community service aims to apply the joint and by-product cost calculation method in the production process of one of the tofu MSMEs, Pabrik Tahu 212, located in Nagari Cupak. The main product produced is tofu, while tofu dregs, as a by-product, are utilized as cattle feed. The activity was carried out through the collection and analysis of production cost data, including raw materials, direct labor, and overhead costs. A cost allocation method was used to separate the costs between the main product and the by-product.